Penerapan Metode Simple Additive Weighting (SAW) dan Rank Order Centroid Dalam Analisis Kinerja Pegawai Honorer - Emellika Rahmayana (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2024)
Employee performance is the result of work that has been achieved by an employee based on predetermined criteria. In order for employee performance to achieve its best, leaders in companies or agencies usually conduct performance appraisals, which are carried out by assessing the performance of each employee in achieving the work targets that have been set. However, the assessment is carried out by the leader in general only by giving a direct value based on the direct observation activities of the leader. To assist leaders in assessing outstanding employees, the method used in this research is the Simple Additive Weighting (SAW) method. With this method, the assessment is done by finding the sum of the weights of the performance rating on each alternative. After the performance assessment is completed, the next leader gives rewards to employees who have the best performance scores. By using the Simple Additive Weighting (SAW) method, it is expected to provide a more accurate assessment because it is based on predetermined criteria that can help management provide an assessment for employees who have outstanding performance. The results of the ranking of honorary employee performance appraisals from the 1st to the 11th are Desnila Aryani, Rosdhiana. S., M. Azhari Palungun, Bambang Indrawijaya, Amri Lubis, Wandani Batubara, Selamet Priyadi, Didi Susanto, Azhari, Fitriani Harahap, Robi Syahad N., and SE.